Thermal studies on solid 2-chlorobenzylidenepyruvate of lighter trivalent lanthanides - Bannach, G. [UNESP]; Mendes, R. A. [UNESP]; Ionashiro, E. Y. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Schnitzler, E. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2005)
Solid compounds of general formula LnL3 for La and Ce and LnL3·nH2O for Pr, Nd and Sm where Ln stands for trivalent lanthanides, L is 2-chlorobenzylidenepyruvate and n=2, 3 and 2 respectively, have been synthesized. On heating these compounds decompose in two or five steps. They lose the hydration water in the first step and the thermal decomposition of the anhydrous compounds occurs with the formation of the respective oxide, CeO2, Pr6O11 and Ln 2O3 (Ln=La, Nd, Sm) as final residue. The dehydration enthalpies found for these compounds (Pr, Nd and Sm) were: 140.1, 148.2 and 221.3 kJ mol-1, respectively. © 2005 Akadémiai Kiadó, Budapest.
Keywords: 2-chlorobenzylidenepyruvate; Lighter lanthanides; Thermal behaviour; Dehydration; Enthalpy; Pyrolysis; Rare earth elements; Synthesis (chemical); Thermoanalysis; Spectroscopic parameters; Thermal behavior; Organometallics